Arachidonic acid is associated with dyslipidemia and cholesterol-related lipoprotein metabolism signatures - Li, Fan; Wang, Yu; Yu, Huahui; Gao, Xiaoqian; Li, Linyi; Sun, Haili; Qin, Yanwen (Frontiers in Cardiovascular Medicine, 2022)
Introduction Abnormal lipoprotein metabolism is associated with a variety of diseases, cardiovascular disease in particular. Free fatty acids (FAs) and triglycerides (TGs) are the principal lipid species in adipocytes and are the major components of lipoproteins. However, in routine clinical laboratory testing, only the total plasma concentrations of FAs and TGs are typically measured. Methods We collected 965 individuals with hyperlipidemia plasma and clinical characteristics; high-throughput metabolomics permits the accurate qualitative and quantitative assessment of a variety of specific FAs and TGs and their association with lipoproteins; through regression analysis, the correlation between multiple metabolites and routine measured lipid parameters was found. Mice were fed a diet containing AA, and the concentrations of TC and TG in the plasma of mice were detected by enzyme method, western blot and qRT-PCR detected the protein and mRNA levels of cholesterol synthesis and metabolism in mice. Result Using LC-MS/MS identified eight free FA and 27 TG species in plasma samples, the plasma concentrations of free arachidonic acid (AA) and AA-enriched TG species were significantly associated with the plasma low-density lipoprotein-cholesterol, apolipoprotein B (ApoB), and total cholesterol (TC) concentrations after adjustment for age, sex, the use of lipid-lowering therapy, and body mass index. AA-rich diet significantly increased the plasma concentrations of TC and ApoB and the liver expression of ApoB protein and reduced the protein expression of ATP binding cassette subfamily G members 5 and 8 in mice. Discussion In this study, it was clarified that the plasma concentrations of free AA- and AA-enriched TG species were significantly associated with the plasma low-density lipoprotein-cholesterol, ApoB, and TC concentrations in individuals with hyperlipidemia, and it was verified that AA could increase the plasma TC level in mice. Taken together, these findings suggest a potential role of AA in the regulation of plasma cholesterol and lipoprotein concentrations.